2020
DOI: 10.3233/jad-200574
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Multi-Component Cognitive Stimulation Therapy (SADEM) in Community-Dwelling Demented Adults

Abstract: Background: Dementia is a persistent, progressive state of cognitive decline against which pharmacological intervention has a modest efficacy, reducing behavioral but not cognitive symptoms. Therefore, different non-pharmacological therapies have been developed; the most scientifically recognized are cognitive therapies that have improved cognitive function and daily life activities. Objective: To evaluate the effectiveness of a multicomponent cognitive stimulation therapy (SADEM) on cognitive and behavioral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Previous randomised controlled studies and meta-analysis of randomised controlled studies indicate that the CST improve cognitive functions (Woods et al, 2012;Aguirre et al, 2013;Lin et al, 2018;Sarageh et al, 2022), Mood (Yamanaka et al, 2013) and quality of life (Yamanaka et al, 2013;Lin et al, 2018) and the effect can be maintained after three months (Lin et al, 2018). In addition, CST could reduce depression among older people with dementia (Sarageh et al, 2022;Alvares-Pereira et al, 2020;Capotosto et al, 2017;Juárez-Cedillo et al, 2020). Furthermore, data from qualitative studies indicate that the group CST improve social interaction, interconnection, happiness, sense of togetherness and enrichment (Lauritzen et al, 2022;Morrish et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous randomised controlled studies and meta-analysis of randomised controlled studies indicate that the CST improve cognitive functions (Woods et al, 2012;Aguirre et al, 2013;Lin et al, 2018;Sarageh et al, 2022), Mood (Yamanaka et al, 2013) and quality of life (Yamanaka et al, 2013;Lin et al, 2018) and the effect can be maintained after three months (Lin et al, 2018). In addition, CST could reduce depression among older people with dementia (Sarageh et al, 2022;Alvares-Pereira et al, 2020;Capotosto et al, 2017;Juárez-Cedillo et al, 2020). Furthermore, data from qualitative studies indicate that the group CST improve social interaction, interconnection, happiness, sense of togetherness and enrichment (Lauritzen et al, 2022;Morrish et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is astonishing that there is a lack of studies on communication-based interventions in dementia [ 297 , 304 ]. Language and/or communication functions are rarely assessed as specific outcome parameters [ 25 , 288 , 290 , 305 , 306 , 307 ] or rather represent higher cognitive functions as fluency tasks [ 306 , 308 ]. Table 2 provides an overview of cognitive language and communication difficulties and resources as AD progresses.…”
Section: Individual Approachesmentioning
confidence: 99%
“…The systematic review by Lobbia et al [ 290 ] showed moderate evidence for CST on language production and comprehension, communication skills and quality of life for people with mild to moderate AD, partly even with long-term-effects in studies published after this review [ 305 , 306 ]. These beneficial effects can possibly be attributed to the focus of CST on language activities and communicative interaction between group participants [ 290 , 309 ].…”
Section: Individual Approachesmentioning
confidence: 99%
“…The aim of intervention for MCI is to decrease the rate of conversion from MCI to AD [85]. Strikingly, in MCI, music therapy had the highest probability of being the best treatment for global cognition, followed by acupuncture and then exercise, among potential pharmacological (including AChE inhibitors) and nonpharmacological treatments, but cognitive interventions were not included [64].…”
Section: Treatment In Different Ad Stagesmentioning
confidence: 99%
“…The aim of the treatment in the mild-to-moderate phase is to preserve cognition and delay disease progression as much as possible. For example, multicomponent cognitive stimulation in participants with mild-stage dementia had not only positive effects on cognition and behavior but also delayed disease progression for at least two years [85]. The combination of several modalities was also effective; for example, in individuals with predominantly mild AD, an integrated program focused on cognitive training, art therapy, and music therapy improved multiple domains such as cognition, depression, anxiety and activities of daily living [86].…”
Section: Treatment In Different Ad Stagesmentioning
confidence: 99%